Tinjauan Yuridis Atas Tidak Dilaksanakannya Musyawarah Desa dalam Penetapan Program Pembangunan di Desa Kembang Mekar Sari - Anwar Anwar; Muannif Ridwan; Bambang Sasmita Adi Putra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The principle of a state governed by law, as stipulated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, requires that every act of governance, including at the village level, be carried out lawfully and without arbitrariness. The village deliberation (musyawarah desa) constitutes the highest decision-making forum, characterized by participation, inclusiveness, and transparency, meaning that development programs should be established through this mechanism. However, in Kembang Mekar Sari Village, indications were found that development programs were determined without holding a village deliberation, raising legal concerns regarding their validity. This study aims to examine the legal framework governing village deliberations, the practices observed in the field, and the legal consequences arising from their non-implementation. The method applied is normative legal research using a library research approach, descriptive-analytical in nature, employing statutory and conceptual approaches. The findings reveal that village deliberation is a binding legal obligation rather than a mere administrative formality. Its neglect produces two consequences: procedural defects that may undermine the policy's validity under administrative law, and the erosion of social legitimacy due to diminished public trust. The weak supervisory function of the Village Consultative Body further aggravates this condition. The study concludes that the practice in Kembang Mekar Sari Village reflects a deviation from the principle of the rule of law and the general principles of good governance, necessitating renewed enforcement of the obligation to conduct village deliberations.